Autocracy and resistance in the internet age - Vanderhill, Rachel (Lynne Rienner Publishers, Inc., 2020)
"Explores in detail how social media are both aiding and undermining autocratic regimes in the Middle East, North Africa, and the former Soviet republics"-- Provided by publisher
Keywords: Authoritarianism -- Former Soviet republics.; Authoritarianism -- Russia (Federation); Authoritarianism -- Middle East.; Internet -- Political aspects -- Former Soviet republics.; Internet -- Political aspects -- Russia (Federation); Internet -- Political aspects -- Middle East.; Social media -- Political aspects -- Former Soviet republics.; Social media -- Political aspects -- Russia (Federation); Social media -- Political aspects -- Middle East.; Autoritarisme -- Ex-URSS.; Autoritarisme -- Russie.; Internet -- Aspect politique -- Ex-URSS.; Internet -- Aspect politique -- Russie.; Médias sociaux -- Aspect politique -- Ex-URSS.; Médias sociaux -- Aspect politique -- Russie.; Authoritarianism; Internet -- Political aspects; Social media -- Political aspects; Middle East; Russia (Federation); Soviet Union -- Former Soviet republics